Advanced manufacturing techniques using laser material processing - Akinlabi, Esther Titilayo, 1976-; Mahamood, Rasheedat Modupe, 1973-; Akinlabi, Stephen Akinwale, 1973- (Advances in civil and industrial engineering (ACIE) book series., 2016)
"This book explores the latest methodologies for using lasers in materials manufacturing and production, the benefits of using lasers in industrial settings, as well as future outlooks for this technology"--